A case study of Petronas as Multinational Corporation (MNC) in Malaysia-Sudan relation / Noordiyana Mohd Saufi - Mohd Saufi, Noordiyana (Faculty of Business and Management, 2010)
PETRONAS, the acronym for Petroliam Nasional Berhad is a national oil company of Malaysia that transformed from being a mere manager and regulator of the country's upstream sector to become an integrated oil and gas multinational corporation. As a state-owned entity, PETRONAS is responsible for the effective management of Malaysia's oil and gas resources, to add value to this national asset and to ensure the orderly and sustainable development of the country's petroleum industry. The company vision is 'to be a Leading Oil and Gas Multinational of Choice'. For PETRONAS to realize its vision of a leading oil and gas multinational of choice, the company embarked in international operation and for this study, Sudan has been identified. Sudan is Africa's largest country, bordering nine other countries which is Libya, Egypt, Eriteria, Ethiopia, Chad, Kenya, Uganda, Democratic Republic of the Congo, and Central African Republic. In this study, Sudan has been identified as the one of the focus country that had contributed to PETRONAS highest investment in international operations.